A Cadet's Honor: Mark Mallory's Heroism - Sinclair, Upton, 1878-1968 (Salt Lake City, UT : Project Gutenberg, 2011)
"A Cadet's Honor: Mark Mallory's Heroism" by Upton Sinclair is a novel written in the early 20th century. The story centers around Mark Mallory, a cadet at West Point, who finds himself embroiled in a series of conflicts and challenges that jeopardize his honor and reputation. As he navigates the harsh realities of cadet life, including hazing and competition, the narrative explores themes of bravery, integrity, and friendship against the backdrop of military training. The opening of the book introduces the cadets as they gather for a significant meeting to discuss the perceived misconduct of Mark Mallory. The discussion reveals that Mark has been accused of insubordination, leading the yearlings (upperclassmen) to plot a punishment against him. As tensions escalate, we see Mark's determination to defend his actions and maintain his honor, despite the collective scorn of his peers. The dynamics between the various characters, including Mark's friends and the antagonists from higher classes, set the stage for a story filled with conflict, heroism, and the struggle to uphold one$1 (Bs values in the face of adversity. (This is an automatically generated summary.)s
Release date is 2011-05-13
E-text prepared by Steven desJardins and the Online Distributed Proofreading Team
Keywords: Conduct of life -- Juvenile fiction; Swimming -- Juvenile fiction; Friendship -- Juvenile fiction; Revenge -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Students -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Soldiers -- Juvenile fiction; Courage -- Juvenile fiction; Hazing -- Juvenile fiction; Parent and child -- Juvenile fiction; Honor -- Juvenile fiction; United States Military Academy -- Juvenile fiction; Fighting (Psychology) -- Juvenile fiction